ANALISIS PENGARUH CORPORATE GOVERNANCE, RELATED PARTY TRANSACTION, KONSENTRASI KEPEMILIKAN DAN NILAI PERUSAHAAN TERHADAP TINGKAT ASIMETRI INFORMASI - Hermi Hermi; Emayanti Christina Hutabarat (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2017)
This research examines to analyze the impact of Corporate Governance, Related Party Transaction, Ownership Concentration, Corporate Value On The Level of Asymmetric Information .The results of this study indicate that (1) Corporate governance is no negative influence on to increase information asymmetry. (2) Related party transaction is no positive influence to increase information asymmetry(3) Ownership concentration is positive influence to increase information asymmetry (4)The corporate value is no negative influence to increase information asymmetry